IMPLEMENTATION OF RESTORATIVE JUSTICE BY LAW ENFORCEMENT IN MINOR THEFT CASES IN MALINAU DISTRICT: - Dwi Apsyanda Putra L. Agung; Marwiah Marwiah; Novita Majid Novita Majid; Jamil Jamil (SOSIOEDUKASI, 2026)
This study aims to analyze the implementation of restorative justice by law enforcement officers in handling minor theft cases in the jurisdiction of Malinau District Police. The research uses a qualitative approach with a descriptive method. Data were obtained through interviews, observation, and documentation involving police officers and community members. The results show that the application of restorative justice has been carried out through mediation between perpetrators and victims, focusing on recovery rather than punishment. However, its implementation still faces several obstacles, including limited understanding among law enforcement officers, lack of clear technical guidelines, and community perceptions that still emphasize retributive justice. The study concludes that restorative justice can be an effective alternative in resolving minor criminal cases, particularly theft, as it promotes social harmony and reduces prison overcrowding. Strengthening regulations, increasing capacity of law enforcement, and public education are needed to optimize its implementation.